Stability and micro‐topographic effects of Sophora moorcroftiana population on a restored alluvial fan, Southern Tibetan Plateau. (19th February 2021) - Liao, Chengrui; Li, Haidong; Lv, Guoping; Tian, Meirong; Tian, Jiarong; Shi, Huihui; Xu, Yannan
Abstract: The Tibetan Plateau, a vulnerable eco‐region undergoing global change, is hard to revegetate where land has become desertified due to the harsh habitat conditions. Sophora moorcroftiana shrubs, which are widely distributed in the middle reaches of the Yarlung Zangbo River basin of Tibet, China, have been naturally restored on desertified land during the last few decades. However, the influences of micro‐topography on the distribution and structure of the S. moorcroftiana population have been rarely reported. Here, we first describe the spatial variation of S. moorcroftiana population on a restored alluvial fan, and then explore the effects of micro‐topography on the restored S. moorcroftiana population, through a series of field surveys combined with the data collected by terrestrial laser scanning. The results indicate that the dominant age structure was adult shrubs (30–60 cm). Although the topographic effect had no significant impacts on soil organic matter and some other structural traits, which remained stable on the restored alluvial fan, it changed population density, plant growth, and distribution. The habitat conditions on the southwest aspect wapproximately 20°–25° slope with altitudes ranging between 3, 593–3, 643 m, conditions that mostly favouring the distribution of the shrub population. The micro‐topography played an important role in species distribution and growth of the S. moorcroftiana population. Our findings could help to understand the effect of micro‐topography on plant population structure and distribution for ecological restoration of desertified land in the Southern Tibetan Plateau.